2015
DOI: 10.1093/mnras/stv1878
|View full text |Cite
|
Sign up to set email alerts
|

Searching for OH maser emission towards the MIPSGAL compact Galactic bubbles

Abstract: We conducted radio observations searching for OH 18-cm maser emission from a sample of 169 unclassified MIPSGAL compact Galactic bubbles. These sources are thought to be the circumstellar envelopes of different kinds of evolved stars. Our observations were aimed at shedding light on the nature of MIPSGAL bubbles, since their characterisation is a fundamental aid for the development of accurate physical models of stellar and Galaxy evolution. The maser emission is observatively linked to the last stages of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Eleven MBs are in common between our samples; however, for seven of them, the authors were unable to calculate the spectral index and did not resolve them, which left only four to produce useful information. Ingallinera et al (2015) showed that the nature derived from radio observations for MB3736 and MB4552 is consistent with the nature of the central sources we identified in Table 6. The other two, MB4589 and MB4607, do not agree with any of the possible central sources that we listed.…”
Section: Identifying the Central Sourcessupporting
confidence: 83%
See 2 more Smart Citations
“…Eleven MBs are in common between our samples; however, for seven of them, the authors were unable to calculate the spectral index and did not resolve them, which left only four to produce useful information. Ingallinera et al (2015) showed that the nature derived from radio observations for MB3736 and MB4552 is consistent with the nature of the central sources we identified in Table 6. The other two, MB4589 and MB4607, do not agree with any of the possible central sources that we listed.…”
Section: Identifying the Central Sourcessupporting
confidence: 83%
“…The other two, MB4589 and MB4607, do not agree with any of the possible central sources that we listed. Ingallinera et al (2015) showed that both MBs have a typical radio morphology of PNe, therefore, it is not possible that the stars we suggested as possible central sources are responsible for the circumstellar envelopes. Since they observed a radio shell, a hot ionizing star (i.e., no later than a B3) would be needed at their centers.…”
Section: Identifying the Central Sourcesmentioning
confidence: 78%
See 1 more Smart Citation
“…Nowak et al (2014) pointed out that, among the MIPSGAL bubbles, about 90 per cent of classified disk nebulae and 60 per cent of ring nebulae are PNe, and conversely about 95 per cent of bubbles classified as PN are disk (65 per cent) or ring (30 per cent) nebulae. As we discussed in another work (Ingallinera et al 2015), the difference between disk and ring nebula may be an artefact of the limited resolution of MIPSGAL and many disk nebula would appear as rings in higher-resolution images. Taking into account the radio and MIPSGAL morphology, we propose the five unclassified elliptical bubbles as PN candidates.…”
Section: Elliptical Bubblesmentioning
confidence: 87%
“…射 电谱线的强度分布图与致密电离氢区也有较强的 相关性. 研究发现, 尘泡周围确实存在着致密核, 致 密电离氢区, 脉泽源, IRAS源等较明显的恒星形成 的现象 [33,34,37,83] . 例如, 尘泡N36附近存在着红外暗 云(Infrared Dark Cloud, IRDC) [31] , 而红外暗云示踪 最年轻的恒星形成区; 尘泡N65的壳状环境的致密 团块中栖息着EGO源G35.05+0.35 [32] .…”
Section: 壳层结构上分子气体所示踪的物理信息unclassified